Scientology, Jehovah’s Witnesses, "Cults," and Conspiracy Theories in Russia Before and During the War in Ukraine - Šorytė, Rosita (The journal of CESNUR, 2022)
Russia’s repressive policy against groups labeled as “cults” or “extremist religions” received new impetus from the invasion of Ukraine. It was claimed that “cults,” including the Jehovah’s Witnesses, Scientology, Neo-Pagans, Satanists, and Pentecostals, secretly directed by the American CIA, had organized the Maidan Revolution in Ukraine in 2014, and were exciting Ukrainian anti Russian feelings in 2022. They have also been accused of acts of sabotage in Russia and of preparing a coup against the Putin regime. While these accusations may be regarded as ridiculous by foreign observers, they play a significant role in domestic Russian propaganda. Russian anti-cultists also quote as evidence that they should be taken seriously the support they received before the 2022 war in Ukraine (and, in some cases, even after) by the European anti-cult federation FECRIS, which did condemn the invasion but continued to maintain ambiguous relations with its old Russian friends.